A Self‐Digitization Dielectrophoretic (SD‐DEP) Chip for High‐Efficiency Single‐Cell Capture, On‐Demand Compartmentalization, and Downstream Nucleic Acid Analysis. (27th July 2018) - Qin, Yuling; Wu, Li; Schneider, Thomas; Yen, Gloria S.; Wang, Jiasi; Xu, Shihan; Li, Min; Paguirigan, Amy L.; Smith, Jordan L.; Radich, Jerald P.; Anand, Robbyn K.; Chiu, Daniel T.
Abstract: The design and fabrication of a self‐digitization dielectrophoretic (SD‐DEP) chip with simple components for single‐cell manipulation and downstream nucleic acid analysis is presented. The device employed the traditional DEP and insulator DEP to create the local electric field that is tailored to approximately the size of single cells, enabling highly efficient single‐cell capture. The multistep procedures of cell manipulation, compartmentalization, lysis, and analysis were performed in the integrated microdevice, consuming minimal reagents, minimizing contamination, decreasing lysate dilution, and increasing assay sensitivity. The platform developed here could be a promising and powerful tool in single‐cell research for precise medicine.